The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s10439-016-1693-4
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Treatment Modulates Mechanically-Induced Injury and Inflammation in Respiratory Epithelial Cells

Abstract: Mechanical forces in the respiratory system, including surface tension forces during airway reopening and high transmural pressures, can result in epithelial cell injury, barrier disruption and inflammation. In this study, we investigated if a clinically relevant pharmaceutical agent, Simvastatin, could mitigate mechanically induced injury and inflammation in respiratory epithelia. Pulmonary alveolar epithelial cells (A549) were exposed to either cyclic airway reopening forces or oscillatory transmural pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…As described in our previous studies 15 , 16 , 22 , 28 , airway reopening was simulated by propagating air bubbles over the epithelial monolayer in the top chamber. Briefly, the top microfluidic channel was connected to a programmable PHD 2000 syringe pump (Harvard Apparatus, Holliston, MA) and PBS was injected into the top microfluidic channel, to simulate a surfactant-deficient airway fluid.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As described in our previous studies 15 , 16 , 22 , 28 , airway reopening was simulated by propagating air bubbles over the epithelial monolayer in the top chamber. Briefly, the top microfluidic channel was connected to a programmable PHD 2000 syringe pump (Harvard Apparatus, Holliston, MA) and PBS was injected into the top microfluidic channel, to simulate a surfactant-deficient airway fluid.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we used similar techniques to demonstrate that clinically approved drugs, i.e. Simvastatin, can be used to prevent cell injury during reopening 22 . Tschumperlin and collaborators pioneered the use of cell stretching devices to model over-distension injury where primary lung epithelial cells are cultured on a flexible non-porous membrane and exposed to ~12–50% equibiaxial strain 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Statins may exert anti-inflammatory action through inhibition of microglia and astrocytes cells, according to previously described ( Cordle and Landreth, 2005 ; Lindberg et al, 2005 ; Li et al, 2009 ). More precisely, simvastatin have showed its anti-inflammatory properties in different other preclinical studies ( Higuita-Castro et al, 2016 ; Wang et al, 2016 ; Barbosa et al, 2017 ). In addition, Qiu and colleagues ( Qiu et al, 2016 ) showed that simvastatin attenuated neuropathic pain through inhibition of RhoA/LIMK/Cofilin pathway, which is activated after chronic constriction injury and related to actin dynamic regulation ( Qiu et al, 2016 ).…”
Section: Resultsmentioning
confidence: 97%
“…HMG CoA reductase inhibitors (i.e., statins) have also been investigated as a potential therapy in ARDS through protection of the endothelial barrier (118,119). A recent report suggested that statins can also dampen inflammation from injurious mechanical forces during mechanical ventilation (120). Despite benefit in preclinical models, a randomized clinical trial of rosuvastatin versus placebo in sepsis-induced ARDS failed to show a difference in 60-day mortality and was stopped early for futility (121).…”
Section: Resolution and Repair Of Injurymentioning
confidence: 99%